1989
DOI: 10.1507/endocrj1954.36.237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Depletion and Orthostasis on Plasma and Urinary Vasopressin in Normal Subjects.

Abstract: We investigated the effects of sodium depletion and orthostasis on the plasma concentration and urinary excretion of vasopressin (AVP) in eight normal female subjects. After 4 days on a sodium controlled diet (130 mEq/ day), the subjects were placed on a low sodium diet (30 mEq/day) for 3 days and 120mg of furosemide was administered orally on the first day of the low sodium regimen.Sodium depletion in the present study reduced body weight by 1.6 kg and increased hematocrit by 3.5%.A significant (p<0.05) incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been shown that supine to erect posture change as well as ambulation increase AVP levels (Cignarelli et al, 1986, Tsuchihashi et al 1989). Furthermore, it has been shown that plasma AVP levels adjust rapidly within approximately 10 minutes upon posture changes (Pump et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that supine to erect posture change as well as ambulation increase AVP levels (Cignarelli et al, 1986, Tsuchihashi et al 1989). Furthermore, it has been shown that plasma AVP levels adjust rapidly within approximately 10 minutes upon posture changes (Pump et al, 1999).…”
Section: Discussionmentioning
confidence: 99%